The impact of E-wallet usage and digital financial literacy on freelancers' tax awareness: The moderating role of tax regulations - Carissa, Carissa; Gunadi, Carolyn Widya; Lindawati, Ang Swat Lin (Edelweiss Applied Science and Technology, 2026)
This study aims to examine the effect of e-wallet usage and digital financial literacy on tax awareness among freelancers, with digital tax regulation serving as a moderating variable. The research adopts a quantitative approach using a cross-sectional survey design. Data were collected from freelancers who actively use e-wallets for financial transactions and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that e-wallet usage has a significant positive effect on freelancers’ tax awareness, highlighting the role of digital payment platforms in enhancing financial transparency and income traceability. Digital financial literacy also shows a positive influence on tax awareness. Furthermore, digital tax regulation significantly strengthens the relationship between digital financial literacy and tax awareness, demonstrating the importance of supportive and well-integrated regulatory frameworks in the digital economy. In conclusion, the study emphasizes that technological adoption and regulatory support are essential drivers of tax awareness among freelancers. Practically, the findings suggest that policymakers and tax authorities should enhance digital tax systems and promote digital financial education, while digital finance providers can integrate tax-related features into e-wallet platforms to encourage compliance and foster a more transparent freelance economy.